Nigeria : 2013 Article IV Consultation, Staff Report, Press Release and Statement by the Executive Director for Nigeria. (IMF country report ;, 2014)
"Despite recent strong non-oil growth, poverty and income inequality remain high and social and governance indicators are below averages for sub-Saharan Africa. Structural reforms under the Transformation Agenda are ongoing, but significant infrastructure gaps and weak institutional capacity still retard growth prospects. At the same time, vulnerabilities are rising in the buildup to general elections in 2015 and fiscal buffers have been reduced. Meanwhile, GDP is being rebased and structural shifts may suggest a refocus in some policy areas. Outlook and Risks. Growth is expected to remain strong, driven by agriculture, trade, and services. Inflation should continue to decline, in line with a tight monetary policy, and a lowering trend in food prices from higher rice and wheat production. Key downside risks are (i) persistently lower oil revenue from changing global dynamics and lower domestic production; (ii) less prudent fiscal policy through the ongoing political cycle; (iii) ongoing security problems in the North; (iv) uncertainty about the pace of global recovery; and (v) capital flow reversals from the expected unwinding of unconventional monetary policy (UMP) in the advanced economies or increased domestic political risk. Addressing oil theft/production losses. In the event of persistent pressures, the naira should be allowed to adjust and reserve adequacy maintained. Improving competitiveness and productivity to generate inclusive growth will require wide-ranging structural reforms. Three key areas could help promote inclusive growth - increasing the delivery of power, broadening the agricultural production base, and increasing access to finance for SMEs. Support for sectoral growth should be underpinned by improvements in competitiveness rather than by protectionist measures"--Abstract